2021
DOI: 10.2340/16501977-2863
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in men and women who have returned to work after stroke: Assessed with the Fatigue Severity Scale and Mental Fatigue Scale

Abstract: Objective To assess the occurrence of self-reported fatigue among men and women who have returned to work after stroke, and the association between 2 fatigue rating scales. Design A cross-sectional study. Subjects A total of 91 adults (58 men/33 women, mean age 53 years) with mild to moderate disability. Methods: Questionnaires were posted to participants approximately one year after stroke. Fatigue was assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 39 publications
1
10
0
Order By: Relevance
“…Therefore, it is important to understand why some characteristics respond to physical and occupational therapies and rest/sleep, but others do not. It appears that characteristics of fatigue that did not improve over time have a mental component to them that the others do not (Norlander et al, 2021). To perform a task requires not only physical abilities, but the brain must allow the task to be completed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is important to understand why some characteristics respond to physical and occupational therapies and rest/sleep, but others do not. It appears that characteristics of fatigue that did not improve over time have a mental component to them that the others do not (Norlander et al, 2021). To perform a task requires not only physical abilities, but the brain must allow the task to be completed.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with stroke struggle with starting and finishing things even after having sleep or rest because, although they may be physically able to move forward, their mental fatigue does not allow them to complete the task (Norlander et al, 2021). This notion is also reflected in our participants’ comments and in the “frustrated to do things I want” characteristic, which initially improved significantly, but that improvement was not sustained over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those employed before the hemorrhage, 55% had not returned to work, 35% on part time and 10% to full time work ( Western et al, 2021 ). Fatigue (FSS, MFS) was a common complaint among people who had returned to work after a stroke where two-thirds of the women and half of the men reported that fatigue interfered with everyday life ( Norlander et al, 2021 ). From a qualitative study, patients who had suffered a stroke and returned to work commonly reported fatigue, concentration and memory problems and personal change as having an impact on work ability ( Balasooriya-Smeekens et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been revealed that many of those who do resume working after stroke struggle with problems related to fatigue, which can negatively affect their ability to remain working in the long term ( 18 , 19 ). We recently showed that the prevalence of fatigue among people who had returned to work within 1 year after stroke was as high as 42%, and that fatigue interfered with work or other responsibilities ( 20 ).…”
mentioning
confidence: 99%